Contact Analysis of Silicone Rubber Rectangular Ring in the Automatic Tighten Assembly - You, JiaChuan; Lin, JingDong; Xu, DaFa; Hao, WenYuan (Manufacturing Technology Journal, 2016)
According to the uniaxial tension model and coulomb friction theory, by considering the nonlinear mechanical properties of rubber, the effect of deformation quantities of silicone rubber rectangular sealing ring on the assembly torque in tightening assembly process is researched in this paper. A stress-strain numerical model of silicone rubber rectangular sealing ring in small deformation range is established when tightening, on this basis, the numerical model is derived in deformation quantities of rectangular ring and assembly torque. Then having the torque-angle experiments by automatic tightening machine. The results show that, compared with the practical engineering experiment, the numerical model that reveals the relationship between the deformation quantities of the rectangular sealing ring and Assembly torque can reflect the effect of deformation on the assembly torque during the actual assembly process with great accuracy, which has a great reference value for the automatic assembly.
Keywords: Torque-angle; Coulomb friction; Stress-strain; Finite element method; Silicone rubber rectangular sealing ring